Investigations of the Thermal Responsiveness of 1, 4, 2‐Oxathiazoles. Issue 30 (14th September 2015) - Hewitt, Russell J.; Ong, Michelle Jui Hsien; Lim, Yi Wee; Burkett, Brendan A.
Abstract: The first systematic study of the thermal rearrangement/fragmentation of 5, 5‐disubstituted 1, 4, 2‐oxathiazoles into isothiocyanates is reported. Structure–activity relationships reveal that the choice of substituent at the 5‐position of the 1, 4, 2‐oxathiazoles is the predominant factor to influence the ease of fragmentation. Abstract : The first systematic study of the thermal rearrangement/fragmentation of 5, 5‐disubstituted 1, 4, 2‐oxathiazoles into isothiocyanates is reported. Structure–activity relationships reveal that the choice of substituent at the 5‐position of the 1, 4, 2‐oxathiazoles not only influences the ease of fragmentation but may also have mechanistic consequences on the reaction.